Students’ goal orientation and gamification in learning for academic performance: A systematic literature review - Eddy Triswanto Setyoadi; Syaad Patmanthara (Research and Development in Education (RaDEn), 2024)
This systematic literature review investigates the interplay between students' goal orientation, the incorporation of gamification in learning, and their academic performance. Utilizing the Kitchenham SLR methodology, the review encompasses 50 articles from diverse research domains and methodologies. The primary objective is to explore how students' goal orientations are affected by gamification and how these strategies influence their academic outcomes. The selected articles span topics such as achievement goal orientation, student engagement, and the psychological aspects of virtual gamification within educational psychology. The review underscores the potential of gamification to enhance student engagement and motivation, provided that the gamification strategies are carefully crafted to align with students' intrinsic motivations and learning objectives. However, it also cautions against possible adverse effects like increased anxiety or distraction. The paper calls for more research into tailored gamification approaches and their sustained impact on student engagement and performance, offering a compilation of references for further investigation into these themes.